2010
DOI: 10.1051/0004-6361/201015186
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical identification of CN-, the smallest observed molecular anion

Abstract: We present the first astronomical detection of a diatomic negative ion, the cyanide anion CN − , and quantum mechanical calculations of the excitation of this anion by means of collisions with para-H 2 . The anion CN − is identified by observing the J = 2−1 and J = 3−2 rotational transitions in the C-star envelope IRC +10216 with the IRAM 30-m telescope. The U-shaped line profiles indicate that CN − , like the large anion C 6 H − , is formed in the outer regions of the envelope. Chemical and excitation model c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
179
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 27 publications
4
179
3
Order By: Relevance
“…In this case we did not observe the formation of formamide, but instead observed either the formation of protonated aminomethanol or formation of NH 2 CH + 2 . This molecule has not yet been observed, but it may be the precursor of the formation of other species observed: (1) CH 2 NH (observed in 1973; Godfrey et al 1973) through a dissociative recombinant process; and (2) NH 2 CH 2 CN (observed in 2008; Belloche et al 2008) by reacting with the anion, CN − , also detected recently (Agundez et al 2010). …”
Section: Discussionmentioning
confidence: 79%
“…In this case we did not observe the formation of formamide, but instead observed either the formation of protonated aminomethanol or formation of NH 2 CH + 2 . This molecule has not yet been observed, but it may be the precursor of the formation of other species observed: (1) CH 2 NH (observed in 1973; Godfrey et al 1973) through a dissociative recombinant process; and (2) NH 2 CH 2 CN (observed in 2008; Belloche et al 2008) by reacting with the anion, CN − , also detected recently (Agundez et al 2010). …”
Section: Discussionmentioning
confidence: 79%
“…The advantage of the anion photoexcitation method is that PE spectra contain signatures of any nonadiabatic dynamics, which are more difficult to observe in conventional electron attachment. For C 18 H 11 -we show that photoexcitation up to at least 1.5 eV above-threshold is almost exclusively converted back to the ground electronic state of the anion. Further, photodetachment of the anion is shown to be very inefficient compared with photoexcitation and ground electronic state anion recovery, implying a resilience to direct UV-induced electron loss.…”
Section: Introductionmentioning
confidence: 77%
“…Six anions have been detected so far in the ISM: C 6 H − [1][2][3][4][5], C 4 H − [6], C 8 H − [7], C 3 N − [8], C 5 N − [2,5], and CN − [9]. The possibility for atomic anions, such as H − , to be formed in the ISM by REA was first suggested by McDowell [10] in 1961.…”
Section: Introductionmentioning
confidence: 99%